Desarrollo del pensamiento matemático en estudiantes de cálculo integral su relación con la planificación docente - Vergel-Ortega, Mawency; Duarte, Hely Isidro; Martínez-Lozano, José Joaquín (Revista Científica, 2015)
Visualization plays an important role to understand the phenomena that underlie the learning and teaching of mathematics, however, it is not a matter for immediate and easy verification, on the other hand, it is a matter of information processing that describes complexity. This article explores the role that plays the visualization associated with the geometric shapes on the way in which some textbooks that are most widely used in the South-West of Colombia, are in charge of introducing the teaching of fractions during the first levels of basic education. It was observed in the analyzed textbooks an imbalance between the number of activities that promote visually powerful roles and those which power is controlled or non-existent.